2017
DOI: 10.1021/acs.jpcc.7b07444
|View full text |Cite
|
Sign up to set email alerts
|

C–H···O Hydrogen Bonding in Pentamers of Isatin

Abstract: Self-assembled monolayers of 1H-indole-2,3-dione (isatin), 3-methyl 2-oxindole, and 7-fluoroisatin are observed on the Au(111) surface via scanning tunneling microscopy (STM). We observed that isatin forms pentamers with density functional theory providing support for a cyclic structure stabilized by both N−His made between the 7-position C−H acting as the hydrogen bond donor and the 3-position carbonyl as the hydrogen bond acceptor, and calculations show that the isatin pentamer structure is 12 kJ/mol more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 69 publications
4
30
1
Order By: Relevance
“…Tetramers are present both as anomalously large peaks in the mass spectrum and as the predominant building block of surface monolayers observed by STM. This follows a number of previous experiments from our laboratory which show agreement between the size of surface-adsorbed clusters with “magic-number” peak intensities in ESI–MS. , We suggest that the concordance between two very different experimental measurements is evidence that the CBZ tetramers are forming in solution and then (depending on the experiment) either delivered to the surface intact through solution deposition or ionized intact through electrospray.…”
Section: Resultsmentioning
confidence: 99%
“…Tetramers are present both as anomalously large peaks in the mass spectrum and as the predominant building block of surface monolayers observed by STM. This follows a number of previous experiments from our laboratory which show agreement between the size of surface-adsorbed clusters with “magic-number” peak intensities in ESI–MS. , We suggest that the concordance between two very different experimental measurements is evidence that the CBZ tetramers are forming in solution and then (depending on the experiment) either delivered to the surface intact through solution deposition or ionized intact through electrospray.…”
Section: Resultsmentioning
confidence: 99%
“…Because STR is mostly populated with methine C–H carrying greater H-bond-forming ability than those of >CH 2 and −CH 3 , methine C–H of pyranose rings acted as the preferred H-bond donor in C–H···O H-bond. 39 However, such reduced broadening in STR- g -TerPol and the appearance of considerably sharp and intense peaks at 2926, 1385, and 2874 cm –1 (sh) (Figure 3a) were related to the facilitated C–H vibrations of free −CH 3 in STR- g -TerPol, via replacement of −CH 3 ···O H-bonds with stronger methine C–H···O H-bonds, leading to altered mutual C–H/O–H/N–H H-bonding in STR- g -TerPol. Alongside, in both hydrogels, broad peaks within 2010–2210 cm –1 could be assigned to C=NH + and >NH 2 + moieties of AM and AMPS, respectively, which might be ascribed to protein and phosphate monoesters as impurities in STR (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Because STR is mostly populated with methine C−H carrying greater H-bond-forming ability than those of >CH 2 and −CH 3 , methine C−H of pyranose rings acted as the preferred H-bond donor in C−H•••O H-bond. 39 However, such reduced broadening in STR-g-TerPol and the appearance of considerably sharp and intense peaks at 2926, 1385, and 2874 cm −1 (sh) (Figure 3a + moieties of AM and AMPS, respectively, which might be ascribed to protein and phosphate monoesters as impurities in STR (Table S4). Moreover, the −CH 2 − and >CH− units resulted through freeradical polymerization of AMPS, AM, and MBA, which were confirmed from the characteristic peaks within 1.05−1.78/ 2.16−2.70 and 0.84−1.57/2.07−2.62 ppm (Figure 4a,b) in TerPol and STR-g-TerPol, respectively.…”
Section: Acs Omegamentioning
confidence: 99%
“…All calculations were performed with the Q-Chem 5.0 software package. 23 As in our previous studies on this class of molecules, 22 all structures were optimized using the B3LYP exchange-correlation func- tional, along with the 6-311++G(d,p) basis set and Grimme's D3 dispersion correction. 24 The initial geometries of the multimolecular structures were generated to be cyclic n-mers, where n is the number of molecules in the cluster.…”
Section: ■ Methodsmentioning
confidence: 99%
“…19−21 Previous work from our laboratory has demonstrated that metastable cyclic pentamers of isatin form on the Au bond. 22 The current study is of methylated isatin derivatives that are functionalized at the 5 and 6 positions, which are remote from the hydrogen bond contacts that form the isatin pentamer (structures shown in Figure 1). The substitution of a methyl group was chosen to test the effect of a non-hydrogenbonding functional group on the formation of the cyclic pentamers.…”
Section: ■ Introductionmentioning
confidence: 99%